pull down to refresh
x = A(1+a)(1+b)(1+c)
y = B(2+a)(2+b)(2+c)
z = C(3+a)(3+b)(3+c)
\frac{x}{1+a} + \frac{y}{2+a} + \frac{z}{3+a}
=A(1+b)(1+c) + B(2+b)(2+c) + C(3+b)(3+c)
=A(1+b+c+bc) + B(4+2b+2c+bc) + C(9+3b+3c+bc)
1
A + 4B + 9C = 1
A + 2B + 3C = 0
A + B + C = 0
A=0.5
B=-1
C=0.5
x = A(1+a)(1+b)(1+c)
y = B(2+a)(2+b)(2+c)
z = C(3+a)(3+b)(3+c)
\frac{x}{1+a} + \frac{y}{2+a} + \frac{z}{3+a}
=A(1+b)(1+c) + B(2+b)(2+c) + C(3+b)(3+c)
=A(1+b+c+bc) + B(4+2b+2c+bc) + C(9+3b+3c+bc)
1
, so we get a system of equations:A + 4B + 9C = 1
A + 2B + 3C = 0
A + B + C = 0
A=0.5
,B=-1
,C=0.5
.